Synthesis of a novel magnetic nano-scale biosorbent using extracellular polymeric substances from Klebsiella sp. J1 for tetracycline adsorption. (December 2017) - Pi, Shanshan; Li, Ang; Wei, Wei; Feng, Liang; Zhang, Guangshan; Chen, Ting; Zhou, Xue; Sun, Huihang; Ma, Fang
Graphical abstract: Highlights: The synthesis method of a novel nano-scale biosorbent was developed. The maximum adsorption capacity of as-prepared Fe3 O4 /MFX was 56.04 mg g −1 . The adsorption mechanism is predominated by chemical ion exchange and COOH. Abstract: The magnetic nano-scale biosorbent (Fe3 O4 /MFX) was synthesized by the chelation and cross-linking procedure with extracellular polymeric substances (MFX) and Fe3 O4 . Fe3 O4 /MFX possessed the porous structure and numerous functional groups (i.e., amino, carboxyl, and hydroxyl), and its core region had a typical size of ∼11 nm. The maximum adsorption capacity was 56.04 mg g −1 at pH 6.0, 10 mg L −1 of tetracycline, and 160 mg L −1 of Fe3 O4 /MFX. The data is properly fitted by the Langmuir, Freundlich, and pseudo-second-order kinetics models. As elucidated by the model parameters and FTIR analysis, chemical ion exchange and COOH could mainly contribute to the adsorption. Meanwhile, the desorption and regeneration experiments implied the adsorption efficiency decreased by only 3.37–8.37% after five adsorption-desorption cycles, and the detection of iron leaching by ICP-OES showed a fine stability of Fe3 O4 /MFX. Therefore, this technically facile, easily recyclable, and environmentally friendly biosorbent has potential for practical applications in antibiotic removal.